2001
DOI: 10.1111/j.1471-0528.2001.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for third degree perineal ruptures during delivery

Abstract: Objective To determine risk factors for the occurrence of third degree perineal tears during vaginal delivery.Design A population-based observational study. Population All 284,783 vaginal deliveries in 1994 and 1995 recorded in the Dutch National Obstetric Database were included in the study. Methods Third degree perineal rupture was de®ned as any rupture involving the anal sphincter muscles. Logistic regression analysis was used to assess risk factors.Main outcome measures An overall rate of third degree peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
155
3
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(187 citation statements)
references
References 19 publications
(49 reference statements)
22
155
3
6
Order By: Relevance
“…This association is likely due to increased mechanical stress during delivery of a large fetus. Other fetal factors that have been associated with anal sphincter laceration include the presence of shoulder dystocia at delivery and occiput posterior position [17]. In this study, shoulder dystocia was a risk factor for anal sphincter laceration with an adjusted odds ratio of 2.03.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This association is likely due to increased mechanical stress during delivery of a large fetus. Other fetal factors that have been associated with anal sphincter laceration include the presence of shoulder dystocia at delivery and occiput posterior position [17]. In this study, shoulder dystocia was a risk factor for anal sphincter laceration with an adjusted odds ratio of 2.03.…”
Section: Discussionmentioning
confidence: 57%
“…The current rate of anal sphincter laceration of 7.9% is consistent with these reported rates. Other recently published rates have ranged from a low of 1.94% [17] to a high of 17% [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study (7) of the risk factors related to third degree laceration during birth found a significant increase (OR=1.12) when the expulsive period was longer than 15 minutes. The authors concluded that the stretching of perineal muscles for an extended period of time can lead to local ischemia, which can increase perineal ruptures.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is no agreement about which risk factors increase or decrease perineal trauma (5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%